PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA PENUTUR ASING (BIPA) DI PTKIN SE-JAWA DAN MADURA - Muyassaroh, Muyassaroh; Putri, Aldila Rahmita; Fahriani, Dita Karisma (Jurnal Bahasa Lingua Scientia, 2025)
The Indonesian Language Program for Foreign Speakers (BIPA) plays a strategic role in strengthening cultural diplomacy and promoting the internationalization of the Indonesian language. However, the implementation of BIPA programs at State Islamic Religious Higher Education Institutions (PTKIN) across Java and Madura still faces various challenges, such as the absence of specific institutional policies, the lack of a standardized curriculum, limited supporting facilities, and teaching materials that do not meet the needs of foreign learners. This study aims to describe the problems of policy and program implementation at six PTKIN: UIN Sayyid Ali Rahmatullah Tulungagung, UIN Syarif Hidayatullah Jakarta, IAIN Kediri, IAIN Syekh Nurjati Cirebon, IAIN Madura, and UIN Raden Mas Said Surakarta. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation, and analyzed using Miles, Huberman, and Saldana’s interactive model. The findings indicate that BIPA program implementation remains suboptimal. Therefore, policy intervention, institutional strengthening, and the development of an integrative and needs-based BIPA learning model are urgently needed.